Investigating the efficacy of ultrasound-guided ethanol retention technique for endometrioma sclerotherapy and its effect on pro-inflammatory cytokine levels: A single-arm clinical trial (Clinics, 2023)
Background: Endometriosis is a chronic inflammatory disease affecting about 10% of women of reproductive age. Endometrioma is the most common presentation of endometriosis in ovaries.Objectives: Herein, the authors study the effect of the ultrasound-guided ethanol retention technique for endometrioma sclerotherapy and its effect on the plasma levels of pro-inflammatory cytokines.Materials and methods: Each endometrioma was aspirated and washed with 0.9% saline until clearance and then 2/3 of the cyst volume was filled with ethanol 98%. Patients were followed for 3 months. After that, changes in their cyst diameter, dyspareunia, dysmenorrhea, and antral follicular count were assessed. Also, the sera levels of Interleukin 1β (IL-β), IL-6, and IL-8 were assayed before and after the treatment. The primary sera levels were also compared with a control group.Results: In the treatment and control groups, 23 and 25 individuals (respectively) with a matched mean age (p-value = 0.680) were enrolled in the study. Among the laboratory variables, IL-1β (p-value = 0.035), as well as AMH (p-value = 0.002), were lower, and IL-6 (p-value = 0.011) was higher in the endometriosis group compared to the controls. Following the treatment, dysmenorrhea, dyspareunia, and the mean diameter of all cysts were significantly (p-values < 0.001) decreased in the treatment group. Also, right (p-value = 0.022) and left (p-value = 0.002) ovaries' antral follicular counts were increased following the treatment. No significant change was found among any of the investigated laboratory levels (p-value > 0.05).Conclusion: Ethanol retention method is proven to be safe and could improve the clinical status of patients with endometrioma. Although further studies are necessary.